(untitled) (The Review of Diabetic Studies, 2025)
This review article explores the pivotal role of Emergency Medical Technicians (EMTs) in saving lives during disasters and acute crises. EMTs are often the first healthcare professionals to reach patients in time-sensitive emergencies, providing essential pre-hospital interventions that significantly improve survival rates. The article synthesizes evidence on EMT contributions across different crisis contexts, including natural disasters, mass casualty incidents, armed conflicts, pandemics, and road traffic accidents. It highlights their clinical interventions, triage decision-making, rapid transportation, and psychological support functions. Furthermore, the review addresses systemic enablers and barriers, such as training standards, resource allocation, coordination with hospitals, and integration within emergency response systems. Key themes include the effectiveness of EMT protocols in pre-hospital survival, their adaptability in resource-constrained settings, and the importance of technology such as telemedicine in extending their impact. Ethical and professional challenges faced by EMTs in high-risk settings are also discussed. The findings emphasize that EMTs play an irreplaceable role in bridging the gap between the onset of a crisis and definitive hospital care. Ultimately, this review underscores the need for strengthened EMT training, policy support, and global collaboration to enhance crisis response capacity and patient survival outcomes.